Geopolitical anxieties of tourism: (Im)mobilities of the COVID-19 pandemic. Issue 2 (July 2020) - Mostafanezhad, Mary; Cheer, Joseph M; Sin, Harng Luh
Bringing the political geography of tourism to bear on responses to the COVID-19 pandemic, this commentary reveals how the geopolitical anxieties of tourism are mediated by historical geographies of race as well as contemporary geoeconomic relations and the broader pivot to the Asia-Pacific region.